ANALISIS BENTUK DAN FUNGSI EUFEMISME DALAM BAHASA TABU PADA SINIAR “ORMAS” DEDDY CORBUZIER - Endang Sholihatin; Muhammad Arik Sunanul Huda; Syahrul Permana Putra; Akhmad Azrul Arsyadhany; Muhammad Faris Syaifulloh; Muhammad Rizqi Amanan Habibulloh (STKIP Subang, 2023)
This research aims to explain the form and function of euphemisms in Deddy Corbuzier's